Revealed Proprietary Information Disclosure - Zufarov, Rustam (The Accounting Review, 2025)
ABSTRACT I examine whether and to what extent firms credibly disclose proprietary private information ahead of seasoned equity offerings. I assess proprietary information disclosures based on the magnitude of the association between a private information-based proxy and stock returns. Using a difference-in-differences design around the Securities Offering Reform (SOR) of 2005, which relaxed restrictions on disclosures, I find that equity-issuing firms disclose more than twice as much proprietary information post-SOR relative to pre-SOR and relative to the same change for the control firms. I corroborate my findings using major customer identity disclosure and limiting the sample to firms with multiple equity offerings. Results are robust after controlling for information flow from insider trading, institutional investors, and financial analysts. Finally, I document that disclosure of proprietary information leads to a 10–23 percent drop in underpricing. These findings offer new insights into how firms balance the proprietary costs and benefits of disclosure. JEL Classifications: M41; K22; G14.